MOBILE CONTEXTUAL AVATAR: DESAIN PERMODELAN AVATAR KONTEKSTUAL DALAM PLATFORM LAYANAN MOBILE - Ferdiana, Ridi (Proceedings of KNASTIK, 2013)
Avatar become one of the representative of digital communication. The usage of avatar is not only as a representative of the user attributes but also represent the behavior of the users such as emotion, passion, and mood. However, the usage of avatar behavior is depends on the user actions. The avatar have no knowledge about the mood of the user until the user describe the mood through status update or comments. If only, the avatar behavior can be automated thorugh some patterns and contexts, it will help the user to automate their mobile activity. This paper will revisit the usage of avatar in mobility world and propose a model called Mobile Contextual Avatar (MCA). The proposed model will discuss the conceptual technique how the context and pattern usage will help the content developer to model dynamic mobile services.